1995
DOI: 10.1063/1.113799
|View full text |Cite
|
Sign up to set email alerts
|

Differential Al–Ga interdiffusion in AlGaAs/GaAs and AlGaInP/GaInP heterostructures

Abstract: Interdiffusion of Al and Ga in Al0.4Ga0.6As/GaAs and Al0.3Ga0.2In0.5P/Ga0.6In0.4P quantum wells has been investigated by measuring the photoluminescence of samples annealed at temperatures from 850 to 1065 °C with and without an SiO2 cap. At 1000 °C under an SiO2 cap, the Al–Ga interdiffusion coefficient is found to be at least two orders of magnitude larger for an AlGaAs/GaAs quantum well compared to an AlGaInP/GaInP quantum well within the same sample. By comparing calculated photoluminescence shifts with me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 0 publications
0
12
1
Order By: Relevance
“…10 This temperature is much higher than our result for the ZnCdSSe/ZnSSe heterostructure. We found that the superlattice was disordered after 500°C annealing.…”
contrasting
confidence: 60%
“…10 This temperature is much higher than our result for the ZnCdSSe/ZnSSe heterostructure. We found that the superlattice was disordered after 500°C annealing.…”
contrasting
confidence: 60%
“…The Al-Ga interdiffusion coefficient is proportional to the concentration of the triply-charged column III vacancy [9,11,14]. Ga desorption is believed to enhance interdiffusion by introducing column III vacancy in GaAs layer growth process, at the same time, Ga concentration is decreased as the growth temperature increases, which can result in the increase in the Al concentration.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, this approach results in a significant increase in component intermixing in the process of superlattice preparing due to the diffusion length shortening. Tremendous research effort has been focused to optimize the performance of electronic and optoelectronic devices by postgrowth diffusion technology [5][6][7][8][9][10][11], while less attention has been paid to in situ diffusion in superlattice with barrier layers of submonolayer thickness.…”
Section: Introductionmentioning
confidence: 99%
“…The technique was also applied to selective intermixing of InGaP red and GaAs infrared dual ͑QWs͒. 4 It was found that the band gap of the GaAs/AlGaAs QW could be raised above that of the InGaP/͑AlGa͒ 0.5 In 0.5 P QW by selective intermixing while not changing the band gap of the red QW. 5 However, the long annealing time and high annealing temperature ͑Ͼ900°C͒ needed for this intermixing caused defect generation in the phosphorous based compounds such as AlInP which prevented the fabrication of red/IR dual wavelength lasers after the anneal.…”
Section: ͓S0003-6951͑98͒02939-8͔mentioning
confidence: 99%